Epigenetics in normal and malignant hematopoiesis: An overview and update 2017. Issue 4 (20th April 2017) - Goyama, Susumu; Kitamura, Toshio
Abstract : Epigenetic regulation in hematopoiesis has been a field of rapid expansion. Genome‐wide analyses have revealed, and will continue to identify genetic alterations in epigenetic genes that are present in various types of hematopoietic neoplasms. Development of new mouse models for individual epigenetic modifiers has revealed their novel, sometimes unexpected, functions. In this review, we provide an overview of genetic alterations within epigenetic genes in various types of hematopoietic neoplasms. We then summarize the physiologic roles of these epigenetic modifiers during hematopoiesis, and describe therapeutic approaches targeting the epigenetic modifications. Interestingly, the mutational spectrum of epigenetic genes indicates that myeloid neoplasms are similar to T‐cell neoplasms, whereas B‐cell lymphomas have distinct features. Furthermore, it appears that the epigenetic mutations related to active transcription are more associated with myeloid/T‐cell neoplasms, whereas those that repress transcription are associated with B‐cell lymphomas. These observations may imply that the global low‐level or high‐level transcriptional activity underlies the development of myeloid/T‐cell tumors or B‐cell tumors, respectively. Abstract : In this review, we provide an overview of genetic alterations within epigenetic genes in various types of hematopoietic neoplasms. We also summarize the physiologic roles of these epigenetic modifiers during hematopoiesis, and describe therapeutic approaches targeting the epigenetic modifications.